Evaluasi Ketersediaan Fasilitas Pendidikan Tingkat Sekolah Dasar Negeri di Kecamatan Grabag Kabupaten Purworejo Tahun 2014 - Waskita, Anton; , Drs. Priyono, M.Si; , Dra. Umrotun, M.Si (2014)
Educational services in elementary school (SD) has been set in legislation through the Minimum Service Standard (SPM) basic education to ensure the quality of education that implemented by each educational unit. Differences between regulatory condition in the field may occur in practice. This research was conducted in the District of Grabag for the purpose of : (1) to determine the availability of educational facilities of state elementary school, (2) to identify the quality of education in state elementary school, (3) to identify the number of the real needs for educational facilities of state elementary school, and (4) to evaluate the avalailability of educational facilities in the state elementary school in the District of Grabag. The method used in this research is descriptive moethod with secondary data analisys techniques. Institutional data used are the data number of SD, the number of students, teachers, classrooms, number of tables and chairs and other supporting data. The field survey is used to check the result of image interpretation for land use by purposive sampling method. The result indicate that the elementary educational facilities are available in all villages except in the Tlepok kulon village. The service of SD as many as 37 units have also been able to reach the entire area of this district. Comparisons between data availability facilities with regulations based on SPM in PERMENDIKNAS No 15 tahun 2010, the lack of educational facilities occured in component of : SD units, the number of classrooms, and the possible shortage of tables and chairs, while the number of teachers is sufficient. Quality of service (KP) and the Quality of Absorption (KDS) mostly had a good value. The result of evaluation of the facilities using SPM and the real condition shows that lack of SD occured for Tlepok kulon village and there is a shortage classrooms in 6 villages. Teacher shortage occurs because some teacher who teach is an auxilary teacher or wiyata bhakti teacher. The need for a shortage of tables and chairs can not be known with certainty because of incomplete data.